Induction of heme oxygenase-1 (HO-1) and NAD[P]H: Quinone oxidoreductase 1 (NQO1) by a phenolic antioxidant, butylated hydroxyanisole (BHA) and its metabolite, tert-butylhydroquinone (tBHQ) in primary-cultured human and rat hepatocytes - Keum, Y.-S. (2014)
10.1007/s11095-006-9094-2